2016
DOI: 10.1161/circimaging.115.003584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Changes in Cardiac Structure and Function in Mice Treated With Anthracyclines Using Serial Cardiac Magnetic Resonance Imaging

Abstract: Background Anthracyclines are cardiotoxic; however, there are limited data characterizing the serial changes in cardiac structure and function after anthracyclines. The aim of this study was to use cardiac magnetic resonance (CMR) to characterize anthracycline-induced cardiotoxicity (AIC) in mice. Methods and Results This was a longitudinal CMR and histological study of 45 wild-type male mice randomized to doxorubicin (DOX, n=30, 5 mg/kg of DOX/week for 5 weeks) or placebo (n=15). A CMR was performed at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 44 publications
(54 reference statements)
13
62
0
1
Order By: Relevance
“…Farhad et al . found increased myocardial T2 times in mice treated with anthracyclines at 5 weeks after beginning of anthracycline treatment, which resolves upon a 20 week follow‐up …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Farhad et al . found increased myocardial T2 times in mice treated with anthracyclines at 5 weeks after beginning of anthracycline treatment, which resolves upon a 20 week follow‐up …”
Section: Discussionsupporting
confidence: 94%
“…Farhad et al found increased myocardial T2 times in mice treated with anthracyclines at 5 weeks after beginning of anthracycline treatment, which resolves upon a 20 week follow-up. 32 In our opinion, timing of imaging is crucial for interpretation of results. Cardiotoxicity of anthracyclines may not translate into a single long-term pathophysiolic mechanism but may rather consist of several phases.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that early mass increases may be a pathologic finding after anthracycline therapy is consistent with recent studies of adults exposed to anthracyclines,16 25 but differs from prior studies in long-term cancer survivors, which demonstrate reductions in LV mass 5. It is possible that myocardial oedema plays a role in these early changes,26 and it is notable that there was a subsequent decrease in mass by the later time point, which may reflect an evolving process.…”
Section: Discussionsupporting
confidence: 82%
“…To investigate the mechanism of protection, we therefore explored mitochondrial dynamics (fusion/fission) and authophagy 30 . Our TEM analysis revealed that mitochondria from doxorubicin-injected pigs not undergoing RIPC were abnormally small, had irregular and aberrant morphology, and contained a hyper-dense matrix, confirming previous reports 28,31 .…”
Section: Discussionsupporting
confidence: 90%